Synthesis, structure, and magnetic properties of the new ternary nitride BaHfN2 and of the BaHf1-xZrxN2 solid solution - Gregory, D; Barker, MG; Edwards, P; Slaski, M; Siddons, D (1998)
The new ternary nitrides BaHf1-xZrxN2(0≤x≤1) have been synthesized by the solid state reaction of the binary nitrides Ba3N2, HfN, and ZrN and characterized by powder X-ray diffraction. The crystal structure of the end member, BaHfN2, has been refined from powder data. The nitridohafnate crystallizes in the tetragonal space groupP4/nmm(a=4.1279(1) Å,c=8.3816(4) Å,Z=2) and is isostructural with the oxide KCoO2. Hafnium is coordinated to five nitrogens in a distorted square base pyramidal geometry, forming layers of edge-sharing pyramids which stack along thecaxis. Barium is situated between the Hf-N layers and is coordinated to five nitrogen atoms. Samples exhibit temperature-dependent paramagnetism between approximately 8 and 293 K and become superconducting below 8 K. © 1998 Academic Press.